Telaah Hadis tentang Nasab Anak Luar Nikah - Mahdalena Nasrun (Ulumuna, 2014)
The Indonesian Constitutional Court’ decision Number 46/PUU-VIII/2010 about the legal status of “out-of-wedlock born child” based on argumentum a fortiori or al-mafhūm al-muwāfaqah. According to this principle “if a child whose genealogy is not yet clear could still be ascribed to one who claims him/her through istilhaq”, then why not determine a child’s genealogy whose biological father is known”. The problems, however, arises when a child was born out-of-legal wedlock. Can his/her nasab be ascribed to his/her father? This study examines the Prophetic tradition on this matter using takhrij hadith methods. It shows that ḥadīth “al-walad li al-firāshi wa li al-‘āhir al-ḥajr wahtajibī yā Sawdah” is valid (ṣaḥīḥ). This ḥadīth explains that a child can be ascribed genealogically to one who claim him/her as his child. However, such claim cannot result in maḥram relationship with child’s sister. It seems that the Prophet acknowledges the existence of biological father but his nasab cannot be deduced to his child.